Convenient Synthesis of 2-Thioimidazolone/Menadione Conjugates via a Two-Step Sequence Starting with Direct Amination of Menadione - Guk, Dmitry A.; Krasnovskaya, Olga O.; Zyk, Nikolai V.; Beloglazkina, Elena K. (SynOpen, 2020)
A convenient route to conjugates of 2-thiohydantoins and menadione with linkers of various chemical nature through a two-stage reaction sequence (direct amination of the menadione with a functional amine followed by modification of a functional group) is presented. Optimal conditions for the direct amination of menadione using alkyl amines with substituents such as azide, alkyne, hydroxyl, amine, halogen, and carboxyl have been developed. Further modification of selected functionalities using CuAAC or esterification reactions with 2-thiohydantoines has been performed.
Keywords: quinone; direct amination; 2-thio-imidazol-4-ones; click chemistry